PELAKSANAAN PROGRAM TANGGUNG JAWAB SOSIAL PT. ENERGI MEGA PERSADA (EMP) MALACCA STRAIT S.A DI KECAMATAN MERBAU KABUPATEN KEPULAUAN MERANTI TAHUN 2014 - Bustomi "; Ali Yusri (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Sosial dan Ilmu Politik, 2016)
Social Responsibility of Company or of Corporate Social Responsibility ( CSR) is an concept that organization, specially ( but not merely) company is to have various responsibility form to entire/all my me of its importance, which among others is consumer, employees, stockholder, environment and community in all company operational aspect including economic aspect, social, and environment. Therefore, CSR closely related with " development of have continuation", namely a[n organization, especially company, in executing its activity have to base its decision of eye do not pursuant to its impact in economic aspect, for example advantage storey;level or of deviden, but also have to consider environmental and social impact of arising out of its decision, good to short-range and also for longer meter.Execution Of Social Responsibility of Company ( Corporate Social Responsibility/ CSR) by PT. Energi Mega of Persada (EMP) Malacca Strait S.A. This Research aim to to know sejauhmana execution of social responsibility of company/ CSR at PT (EMP) executed pursuant to going into effect as well as to know influence of execution of social responsibility of company/ CSR PT (EMP) to society. This research have the character of research of field with data collecting obtained to [pass/through] interview with company [party/side] and society and also pay attention supporter literature. Pursuant to result of from obtained datas and research, hence obtained by the following result: (1) Execution of social responsibility of company/ CSR PT (EMP) in general have been executed based on rule going into effect namely Number rules and regulations 40 Year 2007 about Limited Liability as regulation which shade execution of social responsibility of company/ CSR in Indonesia and Regulation of Government of Number 47 Year 2012 about Environmental and Social Responsibility of Limited Liability as regulation of its execution. But still there are insuffiency and weakness in its that is, there are him some activity and program which have been planned by company but in its it him not yet walked maximally. and only some of is small the than execution of social responsibility of company/ CSR executed by company board of directors.Keyword: Execution Of CSR, PT. Energi Mega of Persada ( EMP) Malacca Strait S.A